Transnational nomads : how Somalis cope with refugee life in the Dadaab camps of Kenya - Horst, Cindy (Berghahn, 2006)
There is a tendency to consider all refugees as 'vulnerable victims': an attitude reinforced by the stream of images depicting refugees living in abject conditions.